Morphological ontogeny of Trichoribates naltschicki (Acari: Oribatida: Ceratozetidae) - Seniczak, Stanisław; Seniczak, Anna; Kaczmarek, Sławomir (Zootaxa, 2019)
The morphological ontogeny of Trichoribates naltschicki (Shaldybina, 1971) is described and illustrated, based on juvenile and adult specimens from a horse pasture in the steppe of northern Mongolia (Bulgan Province). The juveniles of T. naltschicki lack a humeral organ and a dark pigmented cuticle around the opisthonotal gland opening, which occur in some species of Trichoribatinae. In the adult, seta l” on genua I and II and all tibiae is thick, spine-like and barbed.